Implementasi Kurikulum Merdeka dalam Pendidikan Guru Sekolah Dasar (International Forum of Researchers and Lecturers, 2025)
The Merdeka Curriculum is an educational policy innovation launched by the Minister of Education, Culture, Research, and Technology in 2022 in response to the need for more flexible, contextual, and student-centered learning. Its implementation at the elementary school level involves various parties, especially teachers and principals, in designing and implementing learning that adjusts to the characteristics and potential of students. Curriculum planning is focused on the preparation of individual learning, competency mapping, and the use of contextual teaching modules. Meanwhile, the implementation of the Independent Curriculum includes strengthening intracurricular learning and projects to strengthen the Pancasila Student Profile (P5), formative assessments, and collaboration between teachers. However, in its implementation, teachers face various challenges, such as limited facilities, difficulties in using digital platforms, and not yet optimal understanding of the concept of the new curriculum. Principal training, collaboration, and leadership support are important factors in overcoming these barriers. This article reviews in depth the aspects of planning, implementing, and evaluating the Independent Curriculum at the elementary school level as well as optimization efforts that can be carried out in improving the quality of education in Indonesia.